Exploring the Digital Entrepreneurship Ecosystem in Indonesian Higher Education: Barriers, Enablers, and Strategic Empowerment - Sholihah, Masyithoh Annisaush; Saputri , Isna Ajeng; Istiqomah, Nabila (Journal of Economics and Management Scienties, 2025)
This study explores the configuration of digital entrepreneurship ecosystems in Indonesian higher education institutions (HEIs), emphasizing barriers and enabling factors that shape students’ entrepreneurial engagement. Using an explanatory sequential mixed-methods design, the research integrates quantitative survey data (N = 173) and qualitative interviews to examine entrepreneurial readiness, innovation capacity, and institutional support structures. Findings indicate that students demonstrate high motivation and self-efficacy but face persistent constraints related to mentorship, funding, and technical access. The qualitative phase identifies six recurring challenges—ideation and market-fit, marketing skills, time management, mentoring gaps, technical limitations, and financial barriers—revealing a fragmented yet promising ecosystem. To address these issues, the study proposes the Strategic Empowerment Model for Digital Entrepreneurship (SEM-DE), a four-lever framework emphasizing structured ideation, continuous mentoring, skill-based clinics, and micro-grant schemes. This research contributes a contextualized and actionable model for strengthening university-based entrepreneurship ecosystems and informs policy directions toward inclusive, innovation-driven higher education in emerging economies.